Digital Collaboration Models for Empowering SMEs: Enhancing Public Organization Performance - R. Luki Karunia; Edi Yanto; Johan Hendri Prasetyo; Erfi Muthmainah; Lely Hiswendari; Prima Setiawan; Muhammad Aulia Putra Saragih (Ital Publication, 2024)
This study aims to examine the effectiveness of SiBakul Jogja, a digital platform initiated by the government in Yogyakarta Province, in supporting small businesses and fostering collaboration among various stakeholders. Through interviews and research analysis, we investigate the mechanisms through which SiBakul Jogja facilitates small business growth and innovation. The findings reveal that SiBakul Jogja serves as a comprehensive resource hub for small businesses, offering assistance in record-keeping, advisory services, and fostering partnerships for innovation. Collaboration among government entities, businesses, academics, and the media plays a crucial role in enhancing the platform's impact. Positive outcomes include job creation and improved access to financial resources. However, challenges such as digital skills shortages and internet connectivity issues persist. The novelty of this study lies in its examination of SiBakul Jogja's collaborative approach in alignment with principles of new public service, contributing to improved public service delivery and economic growth. Addressing these challenges collectively presents an opportunity to leverage SiBakul Jogja's potential to significantly boost the local economy. Through effective teamwork and organizational strategies, digital support for small businesses can be optimized, fostering economic growth and resilience. Doi: 10.28991/ESJ-2024-08-04-015 Full Text: PDF